The Role of Islamic Religious Education in the Development of Students’ Mental and Emotional Well-Being - Imam Jafar Shodiq (Badan Usaha Milik Desa Berkaho Pungpungan, 2025)
The increasing prevalence of mental and emotional health issues among students has become more evident in modern educational environments, including at SMA Islam Al-Fattah Pungpungan. Students face academic pressure, the influence of social media, family expectations, and complex social interactions. These conditions give rise to anxiety, stress, burnout, decreased motivation, and emotional instability, all of which impact the learning process and character development. This study aims to analyze the role of Islamic Religious Education (PAI) in fostering students’ mental and emotional well-being, as well as to identify the forms of guidance implemented by PAI teachers both formally and informally. Using a descriptive qualitative approach, data were collected through observation, in-depth interviews, and documentation at SMA Islam Al-Fattah Pungpungan. The findings show that PAI teachers play a significant role as educators, spiritual guides, and moral counselors who provide emotional support, habituation of worship, religious activities, and dialogical learning to strengthen students’ mental stability. The implemented guidance includes reinforcing religious character, enhancing emotional intelligence, managing stress, and creating a conducive and Islamic-based school environment. The implications of this study highlight that Islamic Religious Education contributes strategically to the development of students’ mental health; therefore, schools need to strengthen mental guidance programs rooted in religious values, improve the capacity of PAI teachers, and integrate spiritual approaches into all aspects of student development.